Catalytic Performance of Sulfonated Carbon Catalysts for Hydrolysis of Palm Oil Empty Fruit Bunch - Kiky Corneliasari Sembiring; Yosi Aristiawan; Luthfiana Nurul Hidayati; Haznan Abimanyu; Fauzan Aulia; Anis Kristiani (Jurnal Kimia Sains dan Aplikasi, 2020)
Utilizing lignocellulosic biomass into valuable products, such as chemicals and fuels, has attracted global interest. One of lignocellulosic biomass, palm oil empty fruit bunch (EFB), has major content of cellulose (30-40%), which is highly potential to be a raw material for fermentable sugar production. In this research, a series of sulfonated carbon catalysts with various concentrations of sulfuric acid (H2SO4, 10-30 v/v%) solutions have been successfully prepared and applied for a single stage of heterogeneous acid-catalyzed hydrolysis over microcrystalline cellulose and EFB under moderate temperature condition and ambient pressure. The catalysts’ physical and chemical properties were characterized by using a Thermogravimetric Analyzer (TGA), X-ray diffractometer, surface area analyzer, and Fourier-transform infrared spectrophotometer. The characterization results showed that sulfonated carbon had relatively similar physical properties with the parent of active carbon. The hydrolysis activity of sulfonated carbon catalysts gave various Total Reducing Sugar (TRS). The effects of sulfate loading amount in catalyst samples and various ionic liquids were investigated. The hydrolysis of pure microcrystalline cellulose powder (Avicel) using 30%-sulfonated carbon (30-SC) catalyst in 1-butyl-3-methylimidazolium chloride ([BMIM]Cl) ionic liquid at 150°C yielded the highest TRS of 16.11%. Subsequently, the catalyst of 30-SC was also tested for hydrolysis of EFB and produced the highest TRS of 40.76% in [BMIM]Cl ionic liquid at 150°C for 4 h. The obtained results highlight the potential of sulfonated carbon catalysts for hydrolysis of EFB into fermentable sugar as an intermediate product for ethanol production.